1997
DOI: 10.1007/pl00000592
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock and the role of the HSPs during neural plate induction in early mammalian CNS and brain development

Abstract: We have investigated the early development expressional of the heat shock protein genes (hsps) and HSP synthesis and their role during neuroectoderm induction, differentiation and early CNS formation. The expression and kinetics of 90, 73/71, 47 and 27 HSPs on neuroectoderm differentiation was compared under normal and stressed conditions. The role of HSPs on neuroctoderm cell fate including thermotolerance and apoptosis using a whole in vitro embryo culture system was studied. Hsp expression appears closely l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 78 publications
4
46
0
Order By: Relevance
“…Age-dependent demyelination and astrogliosis in hsf-deficient mice Hsf1 is expressed in neurons, astrocytes, and oligodendrocytes (Walsh et al, 1997;Stacchiotti et al, 1999), whereas Hsf2 is expressed in neurons and glia and the developing cerebral cortex (Stacchiotti et al, 1999;G. Wang et al, 2003;Chang et al, 2006) and Hsf4 is expressed in CNS of developing embryos, certain neuronal cell population, but not in astrocytes ) (data not shown).…”
Section: Resultsmentioning
confidence: 92%
“…Age-dependent demyelination and astrogliosis in hsf-deficient mice Hsf1 is expressed in neurons, astrocytes, and oligodendrocytes (Walsh et al, 1997;Stacchiotti et al, 1999), whereas Hsf2 is expressed in neurons and glia and the developing cerebral cortex (Stacchiotti et al, 1999;G. Wang et al, 2003;Chang et al, 2006) and Hsf4 is expressed in CNS of developing embryos, certain neuronal cell population, but not in astrocytes ) (data not shown).…”
Section: Resultsmentioning
confidence: 92%
“…Further, heat shock-induced phosphorylation of both p38 and HSP27 was reduced in MEKK4 K1361R cells, suggesting an important role for MEKK4 in the heat shock-induced stress response. We could not detect phospho-HSP27 in embryo cryosections, due to the insensitivity of the available antibodies but not due to lack of expression, as HSP27 message is constitutively expressed in the developing central nervous system (21,35). As an in vitro validation of MEKK4 regulation of HSP27, MEKK4 K1361R MEFs exposed to heat shock demonstrated a reduction in the stability of actin microfilaments.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, it is a protective agent under stress conditions and is involved in protein renaturation and refolding (33). In the developing mammalian nervous system, HSP90 is highly expressed in the G 0 phase of cells during neuroectoderm differentiation, suggesting that it is required in order to maintain cells in this phase (34). Moreover, Loones et al (35) have reported the differential expression of HSP90 in various regions of the developing nervous system, suggesting involvement of this molecule in specific functions distinct from its chaperone activity.…”
mentioning
confidence: 99%